High Efficacy of Therapeutic Equine Hyperimmune Antibodies Against SARS-CoV-2 Variants of Concern - Moreira Soto, Andrés (2021)
SARS-CoV-2 variants of concern show reduced neutralization by vaccine-induced and therapeutic monoclonal antibodies; therefore, treatment alternatives are needed. We tested therapeutic equine polyclonal antibodies (pAbs) that are being assessed in clinical trials in Costa Rica against five globally circulating variants of concern: alpha, beta, epsilon, gamma and delta, using plaque reduction neutralization assays. We show that equine pAbs efficiently neutralize the variants of concern, with inhibitory concentrations in the range of 0.146–1.078µg/mL, which correspond to extremely low concentrations when compared to pAbs doses used in clinical trials. Equine pAbs are an effective, broad coverage, low-cost and a scalable COVID-19 treatment.